POWER QUALITY EVOLUTION FOR WIND ENERGY CONVERSION SYSTEMS USING EMBEDDED Z-SOURCE INVERTER AND PERMANENT MAGNET SYNCHRONOUS GENERATOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This study focuses on two key goals: maximising wind power and providing the system with high-quality electricity. A permanent-magnet synchronous generator and an embedded Z-source inverter are used in this setup to increase the voltage. The Permanent Magnet Synchronous Generator is employed for its unique features, including excellent performance, low weight and volume, and the fact that it doesn't require an external power source to excite its permanent magnets. The DC-link embedded Z-Source inverter is used to connect this generator to the electrical grid. Typically, the Z-Source connection requires many turns in the transformer winding; however, in this case, lower-rated windings are used for inductance instead of the transformer. Thus, the voltage gain is also balanced by the parallel capacitances. Moreover, symmetrical voltage and current distribution across the network, as well as reduced voltage stresses, are benefits of embedded technology. The recommended method, the embedded Z-Source inverter, is specifically controlled by a fuzzy logic controller that also tracks the maximum power to the wind system and reduces total harmonic distortion by 0.86%, as recorded in MATLAB. However, results were also confirmed from an experimental prototype perspective.
Keywords: Permanent magnet synchronous generator (PMSG); Embedded Z-source inverter (EZSI); Total harmonics distortion (THD); Fuzzy logic controller (FLC); Z-source inverter (ZSI); Wind energy conversion system (WECS)